2014
DOI: 10.1007/s12639-014-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Are the fatty acids responsible for the higher effect of oil and alcoholic extract of Nigella sativa over its aqueous extract on Trichomonas vaginalis trophozoites?

Abstract: Trichomoniasis, the disease caused by the flagellate protozoan Trichomonas vaginalis is the sexually transmitted infection with the largest annual incidence. Metronidazole is the drug of choice recommended for the treatment of human trichomoniasis but it can lead to drug resistance and many other adverse effects. So, it is necessary for new alternatives for the treatment of this infection. Medicinal plants or herbs could be good alternative regimens to be inexpensive, effective and safe to use. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Aqueous extract of N. sativa was found to possess a remarkable effect on the growth of T. vaginalis . To further elucidate the mechanism and understand the effect of fatty acids of N. sativa, Mahmoud et al (2016) undertook a study to compare the efficacy of N. sativa oil, aqueous extract, and alcoholic extract of N. sativa on T. vaginalis . It was found that N. sativa oil at a concentration of 2 mg/mL, and alcoholic extract at a concentration of 10 mg/mL, exhibited similar activity as that of metronidazole (50 μg/mL) after 24 h. The aqueous extract was found to have less effect on T. vaginalis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous extract of N. sativa was found to possess a remarkable effect on the growth of T. vaginalis . To further elucidate the mechanism and understand the effect of fatty acids of N. sativa, Mahmoud et al (2016) undertook a study to compare the efficacy of N. sativa oil, aqueous extract, and alcoholic extract of N. sativa on T. vaginalis . It was found that N. sativa oil at a concentration of 2 mg/mL, and alcoholic extract at a concentration of 10 mg/mL, exhibited similar activity as that of metronidazole (50 μg/mL) after 24 h. The aqueous extract was found to have less effect on T. vaginalis.…”
Section: Resultsmentioning
confidence: 99%
“…It is presumed that fatty acids in the oil and alcoholic extract may interact with the cell membranes, resulting in transient or permanent variable size pores. This formation of pores results in leakage, reduced nutrient uptake, or cellular respiration inhibition in T. vaginalis ( Mahmoud et al, 2016 ). Thus, oil and alcoholic extract of N. sativa are potentially bioactive against T. vaginalis.…”
Section: Resultsmentioning
confidence: 99%
“…These results agree with Tonkal [36] who found that NsCE has a remarkable inhibitory effect on the growth of T. vaginalis trophozoite. Also Mahmoud et al [28] and Al-Ammash [37] pointed out that NsCE had an in vitro antitrichomanal effect. As the adhesion process plays a crucial role in the pathogenesis of Trichomonas, N. sativa has an anti-adhesion effect for T. vaginalis to human epithelial cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…N. sativa crude extract (NsCE) was prepared from air dried seed, the grounded seeds were soaked in aqueous methanol 85% (1/10w/v) then filtered and the plant residue re-extracted with 50% methanol. Removal of methanol by rotatory evaporator below 40% was used [28].…”
Section: Preparation Of Drugs and Herbsmentioning
confidence: 99%
“…Safety is an important factor limiting the application of some drugs to patients with NAFLD. In contrast, plants or herbs have the characteristics of being cheap, effective, and safe (Mahmoud et al, 2016). NS, as a plant, has not observed adverse effects in most clinical trials (Tavakkoli et al, 2017), even in patients with chronic kidney disease stage 3 and demonstrate the safety, efficacy, and quality of marketed products.…”
Section: Discussionmentioning
confidence: 99%